Microstructure and mechanical properties of SiC fibres after exposure at elevated temperature. (16th November 2016) - Liu, Y.; Fu, Q.; Li, L.; Shen, Q.; Li, H.; Li, K.
Abstract : To understand the service behaviour of SiC fibres, the effects of ambient environment and temperature on the microstructure, mechanical property and oxidation behaviour of these fibres were investigated. The result shows that, the surface of SiC fibres becomes rough after exposure in air from 973 to 1573 K due to the formation of small SiO2 particles, and a smooth SiO2 film will be formed on the SiC fibre at 1773 K. In Ar atmosphere, SiC fibres will change into clusters of large SiC crystals after heat treatment for 2 h at 2373 K. The tensile strength of SiC fibres decreased by 66 and 95% when the fibres were exposed at 1773 K for 5 min in air and 2373 K for 2 h in Ar, respectively. This degradation is associated with the evaporation of CO and SiO from the fibres as well as with SiC grain growth in the fibres.